New aspect of hepatic nuclear glycogenosis in diabetes. Issue 1 (January 1968) - Caramia, F.; Ghergo, F. G.; Branciari, C.; Menghini, G.
Abstract : Three cases of nuclear glycogenosis in the liver of diabetic patients have been studied by electron microscopy. In addition to the glycogen deposits described by others, an unusual intranuclear glycogen-filled body was found in all three cases. This body occurred alone or in close contact with the major glycogen deposit.